Perlindungan Hukum terhadap Konsumen atas Pembatalan Tiket Keberangkatan Pengangkutan Udara Akibat Pandemi Covid-19 - Putu Inten Kanaya; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2022)
One of the public transportation sectors affected by the COVID-19 pandemic is air transportation. Many cities or countries have imposed a system of lockdown or social distancing in their territory, resulting in almost all flights being cancelled. The purpose of this study is to analyze the form of legal protection for consumers who experience cancellations due to the COVID-19 pandemic? And discussed the form of responsibility of the air transportation company towards the obligation to refund air transportation departure tickets that were canceled due to the covid-19 pandemic. This study uses normative law as its method with conceptual and legislation as its approach. There are three sources used in this research, namely primary, secondary, and tertiary legal materials. The legal materials contain the 1945 Constitution, the Criminal Code, the Consumer Protection Act, the Aviation Law and the Disaster Management Law, the Minister of Transportation, Government Regulations, legal journals, and other legal-related literacy. These materials are collected by means of recording techniques, file systems, and document studies which will later be analyzed systematically. The forms of legal protection listed in the results of this study show a form of legal protection for consumers who experience cancellation of departures due to the COVID-19 pandemic in the form of rights and consumer obligations described in Law no. 1 of 2009 regarding Aviation and Law no. 8 of 1999 regarding Consumer Protection. The responsibility of the air transportation company for the obligation to refund flight departure tickets that were canceled due to the covid-19 pandemic is to apply a refund mechanism in the form of vouchers